Knowledge and Utilization of Aseptic Technique towards Covid-19 Infection Prevention among Primary Healthcare Workers in Ibadan North-East Local Government, Oyo (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The COVID-19 pandemic has put the healthcare system under immense pressure, with primary healthcare workers being at the forefront of the fight against the disease. Healthcare workers face a high risk of contracting COVID-19 due to their close proximity to infected patients. Therefore, knowledge and utilization of aseptic technique is critical for the prevention of COVID-19 transmission among primary healthcare workers. This research was therefore designed to investigate the knowledge and utilization of aseptic technique towards Covid-19 infection prevention among health workers in Ibadan North-East local government, Oyo State. A descriptive cross-sectional study design was adopted to elicit information from the respondents. A pre-tested semi-structured interviewer-administered questionnaire was used to elicit information from 125 consenting respondents who were randomly selected. Data collected was analyzed using SPSS version 20. Majority primary healthcare workers in Ibadan North-East local government were within the age group 18 and 27 years and more than half of them were females. Most were single, Christians, junior staff and had NCE/Diploma as their highest educational qualification. Furthermore, High prevalence of good knowledge, positive attitude and utilization of aseptic technique towards Covid-19 infection prevention were observed among the respondents. This study revealed that there is no association between knowledge and utilization of aseptic technique towards Covid-19 infection prevention among the respondents, also this study also showed that there is no significant association between attitude and utilization of aseptic technique towards Covid-19 infection prevention among the respondents but there was association between the utilization of aseptic technique towards Covid-19 infection prevention and primary healthcare workers. In conclusion, since there was an association between attitude towards utilization of aseptic techniques in preventing Covid-19 infection but they were significantly utilized aseptic technique towards Covid-19 infection prevention. Therefore, arranging training programs for HCWs might be useful in improving their knowledge of infection control standard precautions and is also expected to facilitate positive attitude and practice.